Normal regression of the internal umbilical remnant structures in Standardbred foals. (30th April 2020) - McCoy, Annette M.; Lopp, Christine T.; Kooy, Sarah; Migliorisi, Alessandro C.; Austin, Scott M.; Wilkins, Pamela A.
Abstract: Background: Diseases affecting the internal umbilical remnant are common in foals. Ultrasound is used to diagnose abnormalities of these structures, and to monitor treatment. However, little is known about the progression of normal internal umbilical remnant regression. Objectives: To document normal regression of the umbilical remnant in foals over the first 6 weeks of life. Study design: Prospective, longitudinal cohort study. Methods: Weekly ultrasound examinations were performed beginning at 1 day of age in 34 healthy Standardbred foals. The umbilical vein was measured in cross section just cranial to the external umbilicus, at the level of the liver and midway between these points. The umbilical arteries were measured in cross section just caudal to the external umbilicus, at the apex of the bladder and at the midpoint of the bladder. The urachus was imaged longitudinally as it exited the bladder. Reduction in size over time was evaluated as percentage change in diameter. Results: Structure diameter decreased linearly over time. The largest measurements were at 24 hours of age with a median umbilical vein diameter of 0.83 cm (IQR 0.77‐1.02 cm), median umbilical artery diameter of 0.61 cm (IQR 0.56‐0.70 cm) and median urachal diameter of 1.07 cm (IQR 1.02‐1.14 cm). There was a significant reduction in diameter for all structures (16.0%‐21.9%; corrected P < .001) within the first week of life. Main limitations: All foals were of a single breed, and examinations and measurements were performed by multiple individuals. Conclusions: The internal umbilical remnants (umbilical vein/arteries, and urachus) rapidly regress over the first few weeks of life. The median internal umbilical remnant diameters reported here are smaller than previously reported values, emphasising the importance of accounting for age when diagnosing umbilical abnormalities. In a healthy Standardbred foal, normal structures are difficult to definitively identify via transcutaneous ultrasound by 5‐6 weeks of age.